C5 Sullivan - Universal SCF Kinetic Model - NC 2018.pdf - Gill, Philip (Cranfield University, 2023)
A Universal Kinetic Model for the Nitration of Cellulose Fibers in Mixed Acids Mr. Francis Sullivan ARDEC, US Army
Keywords: 'nitrocellulose'